2021
DOI: 10.1002/ange.202108492
|View full text |Cite
|
Sign up to set email alerts
|

A TiO2‐Co(terpyridine)2 Photocatalyst for the Selective Oxidation of Cellulose to Formate Coupled to the Reduction of CO2 to Syngas

Abstract: Immobilization of ap hosphonated cobalt bis(terpyridine) catalyst on TiO 2 nanoparticles generates ap hotocatalyst that allows coupling aqueous CO 2 -to-syngas (CO and H 2 )r eduction to selective oxidation of biomass-derived oxygenates or cellulose to formate.Anenzymatic saccharification pre-treatment process is employed that enables the use of insoluble cellulose as an electron-donating substrate under benign aqueous conditions suitable for photocatalytic CO 2 conversion. The hybrid photocatalyst consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…9,10 Biomass, including cellulose and lignin, has emerged as an ideal sacri-cial agent due to its abundance, low cost, and renewability. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In the reaction process, the oxidation and decomposition of biomass are the rate-determining steps in the conversion of photocatalytic biomass to H 2, as it has a complex structure and high inertness. To promote the reaction, researchers commonly use highly alkaline conditions 3,18 (10 M NaOH and KOH), which is not conducive to practical application.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Biomass, including cellulose and lignin, has emerged as an ideal sacri-cial agent due to its abundance, low cost, and renewability. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In the reaction process, the oxidation and decomposition of biomass are the rate-determining steps in the conversion of photocatalytic biomass to H 2, as it has a complex structure and high inertness. To promote the reaction, researchers commonly use highly alkaline conditions 3,18 (10 M NaOH and KOH), which is not conducive to practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have reported that lignocellulose is oxidized to HCOOH, owing to the positive valence band position of TiO 2 (3.0 eV vs RHE, PH = 7). [11] Graphitic carbon nitride (g-C 3 N 4 ) has a conduction band (CB) at −1.4 V and a valence band (VB) at 1.3 V that is suitable for most photocatalytic biorefineries. [12] However, pristine g-C 3 N 4 only affords unsatisfactory activity owing to limited visible-light absorption range, fast recombination of photo-excited charge carriers, and low specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, solar-driven photocatalytic H 2 production from lignocellulosic biomass provides a unique approach for the conversion of lignocellulosic biomass to H 2 , which has particularly attracted a lot of attention. In this method, a semiconductor was used as the photocatalyst to accomplish both H 2 generation reaction and lignocelluloses decomposition reaction. That is, the photogenerated electron can reduce protons to H 2 , while the hole can oxidize lignocellulosic biomass to H + , CO 2 , and organics. Because both photocatalyst and lignocellulosic biomass were solids, it is kinetically difficult to realize hole transfer between photocatalyst and lignocellulose owing to the absence of effective chemical collision.…”
Section: Introductionmentioning
confidence: 99%